The N-Terminus of Human Lactoferrin Displays Anti-biofilm Activity on Candida parapsilosis in Lumen Catheters - Fais, Roberta; Di Luca, Mariagrazia; Rizzato, Cosmeri; Morici, Paola; Bottai, Daria; Tavanti, Arianna; Lupetti, Antonella (Frontiers in Microbiology, 2017)
Candida parapsilosis is a major cause of hospital-acquired infection, often related to parenteral nutrition administered via catheters and hand colonization of health care workers, and its peculiar biofilm formation ability on plastic surfaces. The mortality rate of 30% points to the pressing need for new antifungal drugs. The present study aimed at analyzing the inhibitory activity of the N-terminal lactoferrin-derived peptide, further referred to as hLF 1-11, against biofilms produced by clinical isolates of C. parapsilosis characterised for their biofilm forming ability and fluconazole susceptibility. hLF 1-11 anti-biofilm activity was assessed in terms of reduction of biofilm biomass, metabolic activity, and observation of sessile cell morphology on polystyrene microtiter plates and using an in vitro model of catheter-associated C. parapsilosis biofilm production. Moreover, fluctuation in transcription levels of genes related to cell adhesion, hyphal development and extracellular matrix production upon peptide exposure were evaluated by quantitative real time RT-PCR. The results revealed that hLF 1-11 exhibits an inhibitory effect on biofilm formation by all the C. parapsilosis isolates tested, in a dose-dependent manner, regardless of their fluconazole susceptibility. In addition, hLF 1-11 induced a statistically significant dose-dependent reduction of preformed-biofilm cellular density and metabolic activity at high peptide concentrations only. Interestingly, when assessed in a catheter lumen, hLF 1-11 was able to induce a 2-log reduction of sessile cell viability at both the peptide concentrations used in RPMI diluted in NaPB. A more pronounced anti-biofilm effect was observed (3.5-log reduction) when a 10% glucose solution was used as experimental condition on both early and preformed C. parapsilosis biofilm. Quantitative real time RT-PCR experiments confirmed that hLF 1-11 down-regulates key biofilm related genes. The overall findings suggest hLF 1-11 as a promising candidate for the prevention of C. parapsilosis biofilm formation and to treatment of mature catheter-related C. parapsilosis biofilm formation.